Global forests risk to climate and land-use change - Ernest F. Asamoah; Joseph M. Maina; Linda J. Beaumont; Hedley S. Grantham; James E.M. Watson (Biological Conservation, 2026)

Assessment of Bottom Trawl Impacts on the Status of Seabed Communities in European Seas - Jan Geert Hiddink; Sebastian Valanko; Luke Batts; Esther D. Beukhof; Mats Blomqvist; Stefan Bolam; Belén Calero; Michele Casini; Marina Delgado; Jochen Depestele; Joanna Desmidt; Gabriele Di Bona; et al. (Fish and Fisheries, 2026)
Bottom trawling affects seabed habitats, but its large‐scale impacts remain poorly quantified. Assessment of trawling impacts is essential to support monitoring and achieving sustainability objectives under international conventions, sustainable development goals, and seafood certification programs. We present a Europe‐wide quantitative assessment of bottom trawling impacts, accounting for regional seabed‐community sensitivity drivers, across the Baltic, Atlantic, Mediterranean and Black Sea continental shelves. Using two risk‐based indicators of seabed status—Relative Benthic Status determined as benthic community biomass relative to seabed fauna carrying capacity (RBS tot ) and RBS sen (biomass of the 10% most sensitive fauna relative to carrying capacity)—we found substantial regional and habitat differences. The Black, Baltic and Aegean‐Levantine Seas showed low trawling intensity and high seabed status across habitats. In contrast, the Western Mediterranean, Ionian and Central Mediterranean and Adriatic Seas were the most severely impacted. Trawling affected the sensitive species biomass fraction more strongly than the total community biomass. RBS tot was in good condition (here chosen as RBS > 75% for epifauna) for over 79% of habitat‐ecoregion combinations. In contrast, RBS sen met this threshold in only 46% of these. A strong correlation emerged between the mean trawling intensity and RBS tot and RBS sen , allowing the use of SAR to estimate ecosystem status. This relationship can support decisions on where, and by how much, SAR reductions are needed to achieve good environmental status in regions where no detailed assessment is available. Our approach provides a quantitative framework to balance fishery production with ecosystem sustainability, offering tools for environmental and fisheries management in Europe.

Integrating benthic ecological status and spatial planning to guide sustainable bottom-contacting fisheries in the Eastern Mediterranean - Irini Tsikopoulou; Irida Maina; Nadia Papadopoulou; François Bastardie; Chris J. Smith (Frontiers in Marine Science, 2026)
To inform ecosystem-based fisheries management in line with the EU legislation objectives for marine fisheries, we evaluated the ecological outcomes of alternative spatial management scenarios to fisheries that consider the ecological impact of bottom trawling on the benthic ecosystem in the Eastern Ionian Sea. Trawling intensity in terms of swept area ratio (SAR) and benthic community sensitivity were combined to estimate the relative benthic status (RBS). Then, five management scenarios were tested. The scenarios include four static closure scenarios (below 800 m, below 600 m, the least-trawled 10% of fishing grounds, and areas shallower than 150 m), where trawling is completely excluded without fishing effort redistribution, and one with a trawl ban in all marine protected areas, where fishing effort displacement is modelled dynamically. Baseline RBS was high (>0.9 on a scale of 0 to 1 where 1 is unaffected benthic community) in all habitats, reflecting relatively low benthic degradation due to bottom trawling. Excluding bottom trawling from areas shallower than 150 m in depth produced the greatest improvements, while thresholds at 600 or 800 m depth, and the closure of the 10% least-trawled grounds, had no significant effects on benthic ecological status. Closure of trawling in the marine protected areas produced mixed outcomes, with improvements in some habitats but localized declines due to displaced effort in others. Our study demonstrates the value of including benthic indicators in spatial management strategies to guide adaptive, evidence-based fisheries governance, balancing conservation objectives with socio-economic sustainability.

Perspectives on beach seine fishing in the Western Indian Ocean: A review - Gladys M. Okemwa; George W. Maina; Edward N. Kimani; Almubarak Abubakar; Mathew O. Silas; Catherine Mwakosya; Bernadine Everett; Rui J. Mutombene; Janet Mwangata; Hassan Yussuf; Willys Osore (Marine Policy, 2025)

Integrated management of root-knot nematodes on tree tomato - Stanlous Juma Waswa; Waceke J. Wanjohi; Maina Mwangi (Rhizosphere, 2025)

Life Cycle Assessment of an Avocado: Grown in South Africa—Enjoyed in Europe - Sheldon A. Blaauw; André Broekman; James W. Maina; Wynand J. v. d. M. Steyn; William A. Haddad (Environmental Management, 2024)
Food production is known to have significant environmental impacts, with the main contributors residing in the farming and transportation life cycle phases. Of the various food products transported around the world, avocados have increasingly gained attention as a high-commodity superfood. Avocados require specific climatic and agricultural conditions for farming, with the most fertile land and conditions located outside Europe. Consequently, most avocados consumed in Europe are imported over vast geographical distances, with little information available to quantify the environmental impacts of this imported superfood. This paper aims to present the most detailed life cycle assessment results of an avocado cultivated, grown and harvested in the Limpopo Province of South Africa and exported to the European market for sale and consumption. A life cycle assessment was developed for the farming, harvesting, handling, packaging, ripening, transportation, and carbon sequestration potential of the avocado, and it was used to conduct a holistic life cycle assessment. Input data was obtained through an 18-month data collection campaign across the relevant stakeholders. A baseline ‘business-as-usual’ scenario is focused on throughout this study, and scope for optimisation is identified for each life cycle phase where applicable, accompanied by uncertainty analyses. Results show a total carbon input of 904.85 kg CO 2 e/tonne. Mitigating this, 521.88 kg CO 2 e/tonne is offset, resulting in a net carbon footprint of 382.97 kg CO 2 e/tonne with uncertainty ranges of −23.22 to +58.69 kg CO 2 e/tonne, normalised to 57.45 g CO 2 e/avocado grown in South Africa and sold in Europe. The environmental impacts of the avocado industry under consideration are largely mitigated by the “nature first” philosophy of the farming and logistics enterprises, which have made significant investments in reducing emissions. Sensitivity analyses indicate that implementing large-scale renewable energy, using alternative packaging instead of cardboard, and selling avocados unripened could further enable the farming enterprise to achieve Net Zero objectives. These measures could reduce baseline emissions from 382.97 kg CO 2 e/tonne to a theoretical −68.54 kg CO 2 e/tonne, representing a 117.9% decrease. Although this study does not quantify climate change impacts, qualitative analyses suggest that climate change will have a net negative effect on the avocado industry in South Africa. These regions, typically located in micro-climates, are projected to become wetter and warmer, adversely affecting crop phenology, pest control, road conditions, management complexity, farmer livelihoods, and food security. The study recommends large-scale implementation of the optimisation strategies identified to achieve Net Zero objectives and the development of proactive climate change mitigation strategies to enhance the resilience of avocado supply chains to future stressors. These insights are crucial for policymakers, industry stakeholders, and consumers aiming to promote sustainability in the avocado market. Graphical Abstract

Science- and Risk-Based Stability Strategies to Support Product Lifecycle Changes - Lori McCaig; Steven Nowak; Alexander Abbott; Jenny Carhart; Megan E. McMahon; Elke Debie; Hanlin Li; Francis Maina; Andrea J. Ji; Mingkun Fu; Yan Wu; Andrew Lennard; et al. (The AAPS Journal, 2024)

An indicator-based approach to assess sustainability of port-cities and marine management in the Global South - Dinah A. E. Ogara; Joji Morishita; Peter J. Davies; Maina Mbui; Majambo Gamoyo; Nashon Njoroge; Isaac Otieno Chann; Benson Senelwa Igesa; Stephen Odhiambo Ochieng (Frontiers in Marine Science, 2023)
Ports and neighbouring cities function as connectors between land and water and have long accommodated a substantial flow of goods and services. Port cities in the Western Indian Ocean (WIO) region and the Global South (GS) are rapidly and inevitably expanding as the demand for global trade increases. However, this expansion has numerous impacts on the surrounding marine ecosystem and the socio-economic livelihoods of local communities. We propose a framework to evaluate the sustainability of port cities in the WIO region and more broadly for cities in the GS. Through an exploratory approach, a systematic literature review (SLR) was undertaken to identify existing themes on port city and marine ecosystem sustainability indicator frameworks. The results revealed a strong bias towards sustainability publications designed for port cities in Global North. The approach developed from this study focuses on the socio-economic and environmental attributes relevant to ports in the WIO region and for GS countries. This draws from the Drivers, Pressures, States, Impacts and Responses (DPSIR) framework and includes 78 indicators. The indicators are designed to identify and report on the complex land and sea interdependencies of port cities. To test the validity of these indicators their interdependencies were examined through a Causal Network (CN) structure which identified 12 priority DPSIR CN. These were also mapped to the UNSDGs enabling the wider applicability and transferability of the framework. The resulting framework enables port cities in emerging economies to establish robust sustainable reporting systems and provides a framework that offers a unique lens for evaluating interactions embedded in the land and sea continuum.

Status and challenges for sustainable billfish fisheries in the Western Indian Ocean - N. I. Kadagi; N. Wambiji; B. Mann; D. Parker; R. Daly; P. Thoya; D. A. M. Rato; J. Halafo; L. Gaspare; E. A. Sweke; S. Ahmed; S. B. Raseta; et al. (Reviews in Fish Biology and Fisheries, 2022)

Identifying global and local drivers of change in mangrove cover and the implications for management - J. M. Maina; J. O. Bosire; J. G. Kairo; S. O. Bandeira; M. M. Mangora; C. Macamo; H. Ralison; G. Majambo (Global Ecology and Biogeography, 2021)
Background Climate change and human activities continue to drive a widespread decline in global mangrove coverage, undermining their capacity to provide ecosystem benefits. While global and local scale drivers of change on mangroves are widely acknowledged, the relative importance and the exposure of mangroves to climatic, geomorphological, and direct human threats vary spatially. Understanding the role and relative importance of the multiscale and multiple threats to mangroves and how these vary spatially is fundamental for formulating a spatially adaptive approach to their management and conservation. Aim Our study investigated the role of multiple threats on mangroves and the relative exposure. Location Western Indian Ocean (WIO) region. Time period Recent past (2002–2019 and future (2050–2060). Major taxa studied Mangrove. Methods Using satellite‐derived indicators of mangrove condition aggregated over 19 years (2002 to 2019) and 14 proxies of climate, human activity, and geomorphology, we applied machine learning methods to determine the role and relative importance of the change drivers. Using outputs from this deductive statistical process, we applied inductive methods to map mangrove exposure spatially. Results Model results highlight the importance of catchment erosion, human pressure, sea level, and macroclimate as the main drivers of the present‐day ecological condition of mangroves in the WIO. Normalized difference vegetation index (NDVI) was more sensitive to the identified drivers than the vegetation condition index (VCI), with the relative importance of variables varying across the two vegetation indicators. Main conclusions In anticipation of a stronger manifestation of climate change impacts, the resilience of mangroves in the WIO could be improved through adaptive management over time and space. Testing the efficacy of the essential biodiversity variables (EBV) is critical for understanding the mechanisms of ecosystem change and managing biodiversity change.

Socio economic characteristics of cricket farmers in Lake Victoria region of Kenya - Jackline A. Oloo; Afton Halloran; Maina J. Nyongesah (International Journal of Tropical Insect Science, 2021)

Climate‐driven shift in coral morphological structure predicts decline of juvenile reef fishes - Luisa Fontoura; Kyle J. A. Zawada; Stephanie D’agata; Mariana Álvarez‐Noriega; Andrew H. Baird; Nader Boutros; Maria Dornelas; Osmar J. Luiz; Joshua S. Madin; Joseph M. Maina; Oscar Pizarro; Damaris Torres‐Pulliza; et al. (Global Change Biology, 2020)
Rapid intensification of environmental disturbances has sparked widespread decline and compositional shifts in foundation species in ecosystems worldwide. Now, an emergent challenge is to understand the consequences of shifts and losses in such habitat‐forming species for associated communities and ecosystem processes. Recently, consecutive coral bleaching events shifted the morphological makeup of habitat‐forming coral assemblages on the Great Barrier Reef (GBR). Considering the disparity of coral morphological growth forms in shelter provision for reef fishes, we investigated how shifts in the morphological structure of coral assemblages affect the abundance of juvenile and adult reef fishes. We used a temporal dataset from shallow reefs in the northern GBR to estimate coral convexity (a fine‐scale quantitative morphological trait) and two widely used coral habitat descriptors (coral cover and reef rugosity) for disentangling the effects of coral morphology on reef fish assemblages. Changes in coral convexity, rather than live coral cover or reef rugosity, disproportionately affected juvenile reef fishes when compared to adults, and explained more than 20% of juvenile decline. The magnitude of this effect varied by fish body size with juveniles of small‐bodied species showing higher vulnerability to changes in coral morphology. Our findings suggest that continued large‐scale shifts in the relative abundance of morphological groups within coral assemblages are likely to affect population replenishment and dynamics of future reef fish communities. The different responses of juvenile and adult fishes according to habitat descriptors indicate that focusing on coarse‐scale metrics alone may mask fine‐scale ecological responses that are key to understand ecosystem functioning and resilience. Nonetheless, quantifying coral morphological traits may contribute to forecasting the structure of reef fish communities on novel reef ecosystems shaped by climate change.

Simulating streamflow in the Upper Halda Basin of southeastern Bangladesh using SWAT model - Farzana Raihan; Linda J. Beaumont; Joseph Maina; Akm Saiful Islam; Sandy P. Harrison (Hydrological Sciences Journal, 2020)

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

Demonstrating PM2.5 and road-side dust pollution by heavy metals along Thika superhighway in Kenya, sub-Saharan Africa - E. G. Maina; A. N. Gachanja; M. J. Gatari; H. Price (Environmental Monitoring and Assessment, 2018)

Environmental implications of high metal content in soils of a titanium mining zone in Kenya - David M. Maina; Douglas M. Ndirangu; Michael M. Mangala; Johan Boman; Keith Shepherd; Michael J. Gatari (Environmental Science and Pollution Research, 2016)

Scaling metabolism from individuals to reef‐fish communities at broad spatial scales - D. R. Barneche; M. Kulbicki; S. R. Floeter; A. M. Friedlander; J. Maina; A. P. Allen (Ecology Letters, 2014)
Fishes contribute substantially to energy and nutrient fluxes in reef ecosystems, but quantifying these roles is challenging. Here, we do so by synthesising a large compilation of fish metabolic‐rate data with a comprehensive database on reef‐fish community abundance and biomass. Individual‐level analyses support predictions of Metabolic Theory after accounting for significant family‐level variation, and indicate that some tropical reef fishes may already be experiencing thermal regimes at or near their temperature optima. Community‐level analyses indicate that total estimated respiratory fluxes of reef‐fish communities increase on average ~2‐fold from 22 to 28 °C. Comparisons of estimated fluxes among trophic groups highlight striking differences in resource use by communities in different regions, perhaps partly reflecting distinct evolutionary histories, and support the hypothesis that piscivores receive substantial energy subsidies from outside reefs. Our study demonstrates one approach to synthesising individual‐ and community‐level data to establish broad‐scale trends in contributions of biota to ecosystem dynamics.

Air breathing in Magadi tilapia Alcolapia grahami , under normoxic and hyperoxic conditions, and the association with sunlight and reactive oxygen species - O. E. Johannsson; H. L. Bergman; C. M. Wood; P. Laurent; D. G. Kavembe; A. Bianchini; J. N. Maina; C. Chevalier; L. F. Bianchini; M. B. Papah; R. O. Ojoo (Journal of Fish Biology, 2014)
Observations of the Magadi tilapia Alcolapia grahami in hot, highly alkaline Lake Magadi revealed that they air breathe not only during hypoxia, as described previously, but also during normoxia and hyperoxia. Air breathing under these latter conditions occurred within distinct groupings of fish (pods) and involved only a small proportion of the population. Air breathing properties (duration and frequency) were quantified from video footage. Air breathing within the population followed a diel pattern with the maximum extent of pod formation occurring in early afternoon. High levels of reactive oxygen species ( ROS ) in the water may be an irritant that encourages the air‐breathing behaviour. The diel pattern of air breathing in the field and in experiments followed the diel pattern of ROS concentrations in the water which are amongst the highest reported in the literature (maximum daytime values of 2·53–8·10 µM H 2 O 2 ). Interlamellar cell masses ( ILCM ) occurred between the gill lamellae of fish from the lagoon with highest ROS and highest oxygen levels, while fish from a normoxic lagoon with one third the ROS had little or no ILCM . This is the first record of air breathing in a facultative air‐breathing fish in hyperoxic conditions and the first record of an ILCM in a cichlid species.

Ecological mapping and data quality assessment for the needs of ecosystem-based marine spatial management: case study Greek Ionian Sea and the adjacent gulfs - Y. ISSARIS; S. KATSANEVAKIS; M. PANTAZI; V. VASSILOPOULOU; P. PANAYOTIDIS; S. KAVADAS; A. KOKKALI; M. SALOMIDI; A. FRANTZIS; A. PANOU; D. DAMALAS; D.S. KLAOUDATOS; et al. (Mediterranean Marine Science, 2012)
Mapping of ecosystem components (natural and socioeconomic) is a prerequisite for ecosystem-based marine spatial management (EB-MSM). To initiate the process of EB-MSM in the Greek Ionian Sea and the adjacent gulfs, the main relevant ecosystem components were mapped based on existing spatial information and expert judgment. The natural components mapped included habitat types and species targeted for conservation, according to national and European legislation and international agreements. Main human activities/pressures related to fisheries, aquaculture, tourism, and industry were also mapped. In order to assess the quality of data used to map ecosystem components and therefore take into consideration the inherent uncertainty, an assessment of 5 semi-quantitative data indicators based on a pedigree matrix was conducted. Through this qualitative approach we gained information related to the sources, acquisition and verification procedures, statistical properties, and temporal & geographical correlation, along with the collection process quality of the ecosystem components under study. A substantial overlapping between ecological features and human activities was identified, confirming the need for a well-planned approach to marine space management, in order to mitigate conflicts for marine resources and conserve marine ecosystems and their associated goods and services.

Spatial heterogeneity in ecosystem structure and productivity in a moist Kenyan savanna - D. O. Otieno; G. O. K’Otuto; B. Jákli; P. Schröttle; J. N. Maina; E. Jung; J. C. Onyango (Plant Ecology, 2011)

Distribution of Cd and Zn Levels in Soils and Acacia xanthophloea Benth. from Lake Nakuru National Park Kenya - N. Dharani; J. M. Onyari; J. I. Kinyamario; D. M. Maina; K. M. Mavuti (Bulletin of Environmental Contamination and Toxicology, 2010)

Strong relationship between coral bleaching and growth anomalies in massive Porites - TIM R. McCLANAHAN; E. WEIL; J. MAINA (Global Change Biology, 2009)
Reports of coral diseases are increasing and may result from human land use and climate change conditions such as increased water temperature, coral bleaching, runoff from land, and changes in the ecology of heavily fished reefs. We examined a stable coral syndrome or a growth anomaly [ Porite growth anomaly (PGA)] (skeletal tissue anomaly, hyperplasia, or ‘tumor’) that was present in 0–15% of massive Porites colonies in 12 Kenyan reef lagoons. At the level of the calice morphology, this growth anomaly showed larger calices with less distance between calices and some calices with higher than normal numbers of septa, which indicate the influence of microboring organisms. Scanning electron micrographs of affected corals revealed a high abundance of fungal hyphae, a potential microboring pathogenic agent. To test the hypothesis that the PGA covaries with environmental variables, we evaluated its prevalence in relationship to 16 parameters of water quality, temperature, intensity of bleaching, benthic composition, and management at the end of the 2005 warm season. Stepwise regression models found eight environmental variables significantly associated with the frequency of the PGA, and the site's bleaching intensity was the most strongly associated variable. When bleaching intensity was removed from the dataset, the concentration of phosphorus was the one significant and positively associated variable, which suggest that the other significant environmental variables were associated with bleaching and not the growth anomalies. Our hypothetical model of causation is that the patchy loss of symbionts, often associated with bleaching, reduces calcification, increases susceptibility to pathogens, and allows endolithic fungi to perforate the skeleton creating a porous and anomalous growth of the skeleton. Consequently, we suggest that the frequency of skeletal growth anomalies is expected to increase with the frequency of coral bleaching.

Identifying Reefs of Hope and Hopeful Actions: Contextualizing Environmental, Ecological, and Social Parameters to Respond Effectively to Climate Change - T.R. McCLANAHAN; J.E. CINNER; N.A.J. GRAHAM; T.M. DAW; J. MAINA; S.M. STEAD; A. WAMUKOTA; K. BROWN; V. VENUS; N.V.C. POLUNIN (Conservation Biology, 2009)
Priorities for conservation, management, and associated activities will differ based on the interplay between nearness of ecosystems to full recovery from a disturbance (pristineness), susceptibility to climate change (environmental susceptibility [ES]), and capacity of human communities to cope with and adapt to change (social adaptive capacity [AC]). We studied 24 human communities and adjacent coral reef ecosystems in 5 countries of the southwestern Indian Ocean. We used ecological measures of abundance and diversity of fishes and corals, estimated reef pristineness, and conducted socioeconomic household surveys to determine the AC of communities adjacent to selected coral reefs. We also used Web‐based oceanographic and coral mortality data to predict each site's ES to climate warming. Coral reefs of Mauritius and eastern Madagascar had low ES and consequently were not predicted to be affected strongly by warm water, although these sites were differentiated by the AC of the human community. The higher AC in Mauritius may increase the chances for successful self‐initiated recovery and protective management of reefs of this island. In contrast, Madagascar may require donor support to build AC as a prerequisite to preservation efforts. The Seychelles and Kenya had high ES, but their levels of AC and disturbance differed. The high AC in the Seychelles could be used to develop alternatives to dependence on coral reef resources and reduce the effects of climate change. Pristineness weighted toward measures of fish recovery was greatest for Kenya's marine protected areas; however, most protected areas in the region were far from pristine. Conservation priorities and actions with realistic chances for success require knowledge of where socioecological systems lie among the 3 axes of environment, ecology, and society.

The Distribution of Cu and Pb Levels in Soils and Acacia xanthophloea Benth. from Lake Nakuru National Park Kenya - N. Dharani; J. M. Onyari; D. M. Maina; K. M. Mavuti (Bulletin of Environmental Contamination and Toxicology, 2007)

Initial Trends of Bird Assemblages Before and After River Diversion in an Endemic-rich African Forest - N. J. Cordeiro; J. C. Lovett; E. Mulungu; G. G. Maina; J. H. Gerstle (Biodiversity and Conservation, 2006)

Detriments to post-bleaching recovery of corals - T. R. McClanahan; J. Maina; C. J. Starger; P. Herron-Perez; E. Dusek (Coral Reefs, 2005)

Perceptions of resource users and managers towards fisheries management options in Kenyan coral reefs - T. R. McCLANAHAN; J. MAINA; J. DAVIES (Fisheries Management and Ecology, 2005)
The perceptions of Kenyan resource users and managers towards gear and area management were examined through face‐to‐face interviews to identify areas of agreement and disagreement and compare with compliance. Opinions were sought about gears that sustained fish catch, gears discouraged by the government and traditional leaders, and the benefits of area management were sought. There was good agreement among most groups and traditional leaders about the gears discouraged by government, with beach seines and spear guns the most commonly listed. This indicates good agreement between government and traditions, promoted by recent government legislation, but compliance was poor since nearly two‐thirds of fishers used these recently prohibited gears. This was due, in part, to lesser agreement concerning gears that promote a sustainable fishery, with spear guns and beach seines scaled low, but moderately supported in this respect by those fishers that use these gears. These gears persist because of the lack of shared evidence about the yields and sustainability of the various gears and social and economic aspects, such as increased competitiveness and decreased costs of the gears. There is evidence that beach seines lower yields but this gear persists because it is more competitive and has lower costs to the user than the other gears. Spear guns also persist because young and poor fishermen, who cannot afford costs associated with other gears, use them. Government employees scaled the benefits of area, and particularly closed area, management, higher than fishers, which is an issue of conflict but, nonetheless, has good compliance because of the long history of closed area management. For both types of management, shared perceptions alone were insufficient to achieve high compliance, and active enabling and enforcement by managers is needed.

Response of Coral Assemblages to the Interaction between Natural Temperature Variation and Rare Warm-Water Events - T. R. McClanahan; J. Maina (Ecosystems, 2003)

Genetic structure of Lake Magadi tilapia populations - P. J. Wilson; C. M. Wood; J. N. Maina; B. N. White (Journal of Fish Biology, 2000)
The control region of the mitochondrial DNA haplotype frequencies were significantly different among the two separate lagoon populations of Oreochromis alcalicus grahami in Lake Magadi and of O. a. alcalicus from lake Natron, and DNA fingerprint similarity indices were significantly higher for intra‐population comparisons of the two Magadi lagoon populations and the Lake Natron population than the inter‐population similarity indices among these populations. A modified F st measure indicated population sub‐division and the phylogeographic partitioning of the VNTR fragments observed were unique to specific populations further indicating substantial genetic differentiation. The lagoon populations within Lake Magadi demonstrated the same degree of genetic differentiation as either of these populations did to the outgroup (the Lake Natron population). There appears to be limited gene flow between Lake Magadi tilapia populations and this population structure has important implications for protecting locally adapted populations within this unique ecosystem.

Distinct genotypic clusters of heterogeneously and homogeneously methicillin-resistantStaphylococcus aureus from a Greek hospital - P. T. Tassios; A. C. Vatopoulos; A. Xanthaki; E. Mainas; R. V. Goering; N. J. Legakis (European Journal of Clinical Microbiology & Infectious Diseases, 1997)